A mini-UAV VTOL Platform for Surveying Applications - Kuldeep Rawat; Ellis Lawrence (IAES International Journal of Robotics and Automation (IJRA), 2014)
In this paper we discuss implementation of a mini-Unmanned Aerial Vehicle (UAV) vertical take-off and landing (VTOL) platform for surveying activities related to highway construction. Recent advances in sensor and communication technologies have allowed scaling sizes of unmanned aerial platforms, and explore them for tasks that are economical and safe over populated or inhabited areas. In highway construction the capability of mini-UAVs to survey in hostile and/or hardly accessible areas can greatly reduce human risks. The project focused on developing a cost effective, remotely controlled, fuel powered mini-UAV VTOL (helicopter) platform with certain payload capacity and configuration and demonstrated its use in surveying and monitoring activities required for highway planning and construction. With an on-board flight recorder global positioning system (GPS) device, memory storage card, telemetry, inertial navigation sensors, and a video camera the mini-UAV can record flying coordinates and relay live video images to a remote ground receiver and surveyor. After all necessary integration and flight tests were done the mini-UAV helicopter was tested to operate and relay video from the areas where construction was underway. The mini-UAV can provide a platform for a range of sensors and instruments that directly support the operational requirements of transportation sector.